An exploratory factor analysis in measuring external protective factors of resilience in Malaysian adolescents - Sulong, Rose Manisah; Ahmad, Nor Aniza; Che Hassan, Norlizah; Zainudin, Zaida Nor; Ismail, Maimunah (Human Resource Management Academic Research Society, 2020)
Adolescence is a period of stress that invites to psychosocial dysfunctional among adolescents. The effects of uncontrolled psychosocial dysfunctional can contribute to a variety of behavioral and emotional problems. This is alarming because statistics in Malaysia about psychosocial malfunction among adolescents show high rates when they are an important future asset to the nation. Literature suggest that research on protective factors of resilience can help to understand the strength of self as well as to highlight potential in adolescents. In this study, one set of questionnaires has been modified in the context of Malaysia and has been through the back-translation process, face and content validity as well as constructs validity. The construct validity of this study was analyzed using an exploratory factor analysis of 183 adolescents aged 16 years. Findings show that all constructs exceed the requirements for sufficient and significant samples for analysis of subsequent factor exploratory by extracting using the principal component of the analysis via varimax rotation. The analysis found that three factors were extracted for school external protective factors and home external protective factor and two factors have been extracted for peer external protective factor as suggested by Resilience Theory (Benard, 1991). Meanwhile, only two factors have been extracted for community external protection factor compared to the original three factors. The discussion and conclusion of this study are discussed in depth at the end of this article.